Root Resorption in Orthodontics - Genetic Susceptibility? - Maria João Ponces (2011)
OBJECTIVES: External root resorption (ERR) is a condition that can be observed in association with orthodontic treatment. The etiology of root resorption is complex, related with several factors. Some inflammatory mediators, controlled by specific genes, have been associated with bone resorption and in the recruitment of osteoclasts during orthodontic movement (Lee et al., 2007; Abass et al., 2008; Bastos et al., 2009). Particularly the association between polymorphisms in the IL-1B gene and ERR during orthodontic treatment has been referenced in literature. The present paper as the principal objective to present a case of an orthodontic patient, Caucasian, gender male, 15 years old, with positive family history of generalized ERR associated to orthodontic treatment (one sister), and there was therefore need to clarify the role of genetic susceptibility in its pathogenesis. MATERIALS AND METHODS: It was performed a literature review on PUBMED with the key words dental orthodontics resorption genetics, 12 articles were obtained and were included 8 of these. There were also associated with the theme 7 more articles, from the list of related articles. The search was limited to the last 10 years and the English, French and Spanish. RESULTS: As there was positive family history of the ERR was decided to perform a genetic test for determination of single polymorphisms for IL1B gene (TGP, CGC Clinical Genetics Center, Portugal), which revealed the presence of an allele of the IL1B gene - positive result for ERR. The absence of external etiological factors associated with orthodontic treatment was suggestive of possible individual genetic susceptibility. CONCLUSIONS: The identification of individuals with increased susceptibility to ERR should be considered during the orthodontic treatment plan, to allow adjustments necessary in terms of magnitude of the force to be applied, both in terms of duration of treatment.